Intraoperative skeletal traction in the dog - Rovesti, G. L.; Margini, A.; Cappellari, F.; Peirone, B. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
A standard skeletal traction technique was applied to each major segment of the appendicular skeleton of ten fresh dog cadavers. Opposition points and anchorage points for the application of traction were determined for each skeletal segment. Traction was exerted by means of a micrometric traction stand, connected to the limb by bands or a stirrup. Traction was applied to the antebrachium and the tibia through nylon traction bands anchored to the metacarpus and metatarsus, respectively. A traction stirrup applied to the condylar region was used as the anchorage point to load the humerus and femur. Once a peak force of 25 kg weight was achieved, the load was monitored for half an hour to check for any variation. After that, each skeletal segment was osteotomized in the mid-diaphyseal region, and evaluated for any angular malalignment due to a mismatch between the axis of the bone and the applied loading. Any ensuing angular malalignment was successfully corrected by manoeuvres using the traction stand. The technique used in this study to perform intraoperative skeletal traction proved to be reliable and consistent for each segment of the appendicular skeleton.
Keywords: Dog; fracture reduction; skeletal traction